Preparation and Evaluation of Wastelage Using Wet Rice Straw and Cow Dung for Ruminant Feed - Ritu, Fatema Tuj-Johora; Islam, Sharmeen; Islam, S. M. Ariful; Jamee, Dewan Kamruzzaman; Kabir, A. K. M. Ahsan; Khan, Md. Rokibul Islam (Journal of the Bangladesh Agricultural University, 2024)
Preparation of wastelage by ensiling wet rice straw treated with cow dung (CD) and molasses was performed to improve the nutritional value as a quality feed for ruminants. Three different treatments were used as T0 (10% cow dung and 85% wet rice straw), T1 (20% cow dung and 75% wet rice straw), T2 (30% cow dung and 65% wet rice straw), and T3 (40% cow dung and 55% wet rice straw) with 5% molasses based on DM in each treatment to explore physical quality, chemical composition, in-vitro organic matter digestibility (OMD) and metabolizable energy (ME) contents at five different ensiling periods of 0, 30, 45, 60 and 90 days. The use of cow dung and molasses in wet rice straw improved the physical quality, nutritive value, and preservation quality of wastelage. The highest DM, CF, and EE were observed as 41.83%, 18.51%, and 2.88% respectively in T0 and CP was highest as 10.55% in T3 followed by T1 and T2. After ensiling, DM, ash, CF and EE were declined in all of the treatments but the increase of CP content was observed significantly (P<0.05) with increasing the ensiling period from 0 to 90 days. The OMD and ME contents were improved in T1, T2, and T3 compared to T0. The highest OMD and ME values were observed in treatment T3 which were 48.46% and 8.78 MJ/Kg DM, respectively and the lowest values were in (T0) were 38.31% and 7.57MJ/Kg DM respectively. Therefore, proper ensiling of rice straw with CD and molasses can provide an inexpensive, quality of feed and also reduce the waste hazards in our environment. J Bangladesh Agril Univ 19(1): 91–98, 2021 https://doi.org/10.5455/JBAU.9431